2016
DOI: 10.1159/000447826
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Attenuates Retinal Vascular Leakage by Inhibiting Calcium/Calmodulin-Dependent Protein Kinase II Activity in Streptozotocin-Induced Diabetes

Abstract: Background: Curcumin possesses many pharmacological properties including anti-inflammatory effects. Although prior studies indicate that curcumin has beneficial effects for diabetic retinopathy, the mechanism of action is not known. To address this issue, we investigated the effect of curcumin against diabetes-induced retinal vascular damage and its mechanism of action by using cultured retinal Müller cells stimulated with high glucose. Methods: We studied the effects of curcumin in vivo in the retinas of rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 43 publications
(57 reference statements)
1
32
0
Order By: Relevance
“…Recently, various nano formulations of curcumin have been synthesized to overcome these issues. Nanoparticle-loaded curcumin appeared to achieve high permeability, good bioactivity and low metabolism in animal models [25-27]. In the present study, the nanomaterial distearoylphosphatidyethanolamin-polyethylene glycol (DSPE-PEG) was employed as a nanocarrier for curcumin.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, various nano formulations of curcumin have been synthesized to overcome these issues. Nanoparticle-loaded curcumin appeared to achieve high permeability, good bioactivity and low metabolism in animal models [25-27]. In the present study, the nanomaterial distearoylphosphatidyethanolamin-polyethylene glycol (DSPE-PEG) was employed as a nanocarrier for curcumin.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying molecular mechanism of diabetic retinopathy is complex and remains largely elusive, which includes PI3K/Akt, p38 MAP kinase, calcium/calmodulin dependent protein kinase a, NOTCH/Wnt signalling [40-42]. Among them, an active VEGF/PI3K/Akt pathway has been dominated linked to pathological angiogenesis in PDR [28, 43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…PKG-I is produced in macrophages, renal tubular cells, mesangial cells, endothelial cells, cardiomyocytes, vascular smooth muscle cells and other cell types [18]. Recently, studies indicated the protective role of the cGMP/PKG signaling pathway on IRI in cardiomyocytes by modulating several signaling pathways including increased phosphorylation of GSK-3β, ERK and Akt, or modulation of mitochondria K ATP channels [19-21]. …”
Section: Introductionmentioning
confidence: 99%